2015
DOI: 10.1002/cbf.3090
|View full text |Cite
|
Sign up to set email alerts
|

Loss of EGF‐dependent cell proliferation ability on radioresistant cell HepG2‐8960‐R

Abstract: Acquired radioresistance of cancer cells interferes with radiotherapy and increases the probability of cancer recurrence. HepG2-8960-R, which is one of several clinically relevant radioresistant (CRR) cell lines, has a high tolerance to the repeated clinically relevant doses of X-ray radiation. In this study, HepG2-8960-R had slightly lower cell proliferation ability than HepG2 in the presence of FBS. In particular, epidermal growth factor (EGF) hardly enhanced cell proliferation and DNA synthesis in HepG2-896… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Results from other groups confirmed that migration, invasion, proliferation and anti-apoptotic ability is changed accompanied by the acquired radioresistance (10,12,15). Different from the previous studies showing reduced proliferation ability of radioresistant cells (46,47), we found significant increase in proliferation of resistant cells compared to their parental cells. Recently, Tahmasebi-Birgani et al also observed that fractionated irradiation induces the radioresistance, along with the inhibition or enhancement of the proliferative ability, depending on the cellular context (48).…”
Section: Discussionsupporting
confidence: 70%
“…Results from other groups confirmed that migration, invasion, proliferation and anti-apoptotic ability is changed accompanied by the acquired radioresistance (10,12,15). Different from the previous studies showing reduced proliferation ability of radioresistant cells (46,47), we found significant increase in proliferation of resistant cells compared to their parental cells. Recently, Tahmasebi-Birgani et al also observed that fractionated irradiation induces the radioresistance, along with the inhibition or enhancement of the proliferative ability, depending on the cellular context (48).…”
Section: Discussionsupporting
confidence: 70%
“…Song et al reported that miR-7-5p enhance autophagy via EGFR/AKT/mTOR signaling [ 26 ]. In CRR cells, it has been reported that the expression of the EGF receptor and phosphorylation of AKT decreased [ 20 , 27 ], and as reported by Song et al, the mTOR signaling was enhanced [ 28 ]. Conversely, it has been reported that the doxorubicin–resistant cell was down-regulated by the miR-7-5p expression [ 29 ].…”
Section: Discussionmentioning
confidence: 99%